Novel insights into the pathophysiology & treatment of PCOS - Diamanti-Kandarakis, Evanthia; Nader, Shahla; Panidis, Dimitrios (Future Medicine Ltd (Unitec House, 2 Albert Place, London N3 1QB, UK), 2012)
Polycystic ovary syndrome, a state of hyperandrogenism and anovulation affecting approximately 7% of reproductive age-women, has assumed center stage in the field of reproductive endocrinology. This book, authored by renowned physicians in endocrinology, gynecology and reproductive sciences, summarizes current knowledge relating to polycystic ovary syndrome, its management and its adverse long-term consequences.